2017
DOI: 10.21037/atm.2017.05.13
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers in epithelial ovarian cancer diagnosis: from present to future perspective

Abstract: Ovarian cancer (OC) represents the most lethal gynecological cancer and the poor prognosis is often attributable to late diagnosis. The diagnostic approach to woman presenting with pelvic mass is difficult and differential diagnosis often requires invasive histological examination. Serum CA125 and HE4, as well as the most of the other serum biomarkers discovered and validated, are not sufficiently sensitive and specific to make early diagnosis. Moreover, conflicting results exist about the improvement of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 99 publications
0
48
0
Order By: Relevance
“…Factors such as differences in age, gender, comorbid metabolic diseases, diet, and fasting status can significantly impact serum levels of metabolites and proteins [26,27]. Furthermore, metabolomics is particularly susceptible to degradation during sample processing [5]. However, previous research has demonstrated that phospholipids are less impacted by variability in diet and, with the exception of LPA, are stable and resistant to degeneration during processing and storage [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as differences in age, gender, comorbid metabolic diseases, diet, and fasting status can significantly impact serum levels of metabolites and proteins [26,27]. Furthermore, metabolomics is particularly susceptible to degradation during sample processing [5]. However, previous research has demonstrated that phospholipids are less impacted by variability in diet and, with the exception of LPA, are stable and resistant to degeneration during processing and storage [9].…”
Section: Discussionmentioning
confidence: 99%
“…Methods pursued thus far include proteomics, metabolomics, and lipidomics. However, the vast majority of recent research has investigated proteomics-based approaches [5]. While CA-125 and other protein-based biomarkers have demonstrated the most success detecting ovarian cancer thus far, recent studies have found that implementation of CA-125 in ovarian cancer screening protocols have not made an equivocal impact on patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…A feasible way to diagnose cancer at an early stage is to establish a useful and comprehensive diagnostic biomarker. To date, only 2 biomarkers, cancer antigen 125 (CA125) and human epididymis 4 (HE4) have been approved by the Food and Drug Administration as biomarkers for EOC [ 5 ]. Several studies have reported that HE4 has the highest sensitivity for detecting EOC as a single biomarker; while a combined biomarker of CA125 and HE4 is a more accurate predictor of malignancy than either alone [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Optimal debulking surgery in combination with adjuvant chemotherapy is considered the criterion standard for the treatment of advanced ovarian cancer. 4 Suboptimal debulking surgery is related to poor prognosis, and the decision to perform primary versus secondary debulking relies on the extent of the disease and the surgeon's experience.…”
mentioning
confidence: 99%